The Influence of Attributional Beliefs On Indonesian EFL Learners’ Reading Comprehension - Nancy Agatha Florida; Concilianus Laos Mbato (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2020)
This research investigated how Indonesian EFL learners attributed their successes and failures in reading comprehension and whether or not there was any correlation between attributional beliefs and EFL learners’ monitoring strategies in reading. The researchers distributed Attributional Beliefs Questionnaire (ABQ) and Reading Monitoring Strategies Questionnaire (RMSQ) to undergraduate students in the third semester (n=36) of a private university in Kupang, the capital city of East Nusa Tenggara (NTT) Province. The data were analyzed using Pearson Correlation scale. Six students were selected to be interviewed to obtain qualitative data. Based on the results, 56% of students attributed their successes and failures in reading to the internal factors (efforts and strategies) rather than the external ones (reading text and learning environment). There was a moderate and insignificant correlation between attributional beliefs and reading monitoring strategies with r=0.51. It indicated that students need to regulate themselves and navigate their learning based on their attributional beliefs or they would experience learned helplessness. This research offered two implications for the teaching of reading among Indonesian EFL learners. In order to gain a greater opportunity to experience more reading success, language teachers were recommended to introduce attribution concepts and implement all reading strategies to their students.